Phase I study of efineptakin alfa (NT-I7) for the treatment of Kaposi sarcoma - Leonard D’Amico; Martin Cheever; Steven P Fling; Anna Wright; Kathryn Lurain; Ramya Ramaswami; Irene Ekwede; Thomas S Uldrick; Robert Yarchoan; Judith C Kaiser; Angela Shaulov Kask; Manoj P Menon; et al. (Journal for ImmunoTherapy of Cancer)
Background CD4+ T-cell lymphocytopenia and immune dysfunction are factors that drive the onset and persistence of Kaposi sarcoma (KS) in people with (PWH) and without HIV. Standard chemotherapy agents for KS can contribute to increasing CD4+ T cell lymphocytopenia. IL-7 is a cytokine that is essential in T-cell development, proliferation and homeostasis. In PWH, IL-7 administration leads to increased numbers of circulating central memory and naïve T-cell phenotypes.Methods In this multicenter phase I study with a 3+3 dose escalation design, participants with KS with or without HIV received up to four intramuscular injections of IL-7 (NT-I7) every 9 weeks. The primary endpoint of the study was to evaluate safety over three escalating dose levels (DL) of NT-I7 (DL1:480 µg/kg, DL2: 960 µg/kg and DL3: 1200 µg/kg) and identify a maximum tolerated dose. Secondary endpoints included evaluation of antitumor activity per the modified AIDS Clinical Trials Group Criteria and assessment of the effect of NT-I7 on the kinetics of CD4+ and CD8+ T-cells.Results Eight cisgender male participants (five with HIV infection) were enrolled. Six participants were treated at DL1, and two were treated at DL2. The study was closed to accrual after enrolment of the second participant on DL2 due to termination of study funding. Four of the eight participants (three in DL1 and one in DL2) completed all four doses of the NT-I7. With regard to treatment-emergent adverse events (AEs), all participants had <grade 2 AEs, which included injection site reaction and alanine aminotransferase increase. Injection site reaction was a dose-limiting toxicity in one participant at DL1. The overall KS objective response rate to NT-I7 was 42.9% (95% CI 9.9%, 81.6%) and all three responders were PWH. Absolute lymphocyte counts, CD4+ and CD8+ T-cell counts increased among all participants following administration of NT-I7. Participants who experienced a response had HIV and lower CD4/CD8 ratio at baseline and throughout the study as compared with those who did not have KS response to NT-I7.Conclusions Preliminary data demonstrate safety and activity of IL-7 in patients with KS and activity specifically among individuals HIV-associated KS.Trial registration number NCT04893018.